An analysis of the cost-effectiveness of transcatheter mitral valve repair for people with secondary mitral valve regurgitation in the UK - Shore, Judith; Russell, Joel; Frankenstein, Lutz; Candolfi, Pascal; Green, Michelle (Journal of medical economics, 2020)
A proportion of chronic heart failure (CHF) patients will experience regurgitation secondary to ventricular remodeling in CHF, known as functional mitral (MR) or tricuspid (TR) regurgitation. Its presence adversely impacts the prognosis and healthcare utilization in CHF patients. The advent of interventional devices for both atrioventricular valves modifies both aspects. We present an economic model structure suitable for comparing interventions used in MR and TR, and assess the cost-effectiveness of transcatheter mitral valve repair (TMVr) plus guideline directed medical therapy (GDMT) compared with GDMT alone in people with MR. An economic model with a lifetime time horizon was developed based on extrapolated survival data and using New York Heart Association classifications to describe disease severity in people with functional MR at high risk of surgical mortality or deemed inoperable. Cost and utility values (describing health-related quality-of-life) were assigned to patients dependent on their disease severity. The analysis was conducted from a UK National Health Service perspective. An incremental cost per additional quality-adjusted life year (QALY) was estimated, and sensitivity (one-way and probabilistic) and scenario analyses conducted. Compared with GDMT, the use of TMVr results in an additional 1.07 QALYs and an increase in costs of £32,267 per patient over a lifetime time horizon. The estimated incremental cost per QALY gained is £30,057 and would therefore be on the threshold of cost-effectiveness at £30,000 per quality adjusted life year. Thus, from a UK reimbursement perspective, in patients with severe functional MR who are at high risk of surgical mortality or deemed inoperable with conventional surgery, TMVr plus medical therapy is likely to represent a cost-effective treatment option compared with GDMT alone. The choice of device (MitraClip or PASCAL) will need to be confirmed once further clinical data are reported.